Monitoreo de fauna silvestre (aves y reptiles) existentes en la zona alta de la comunidad de Canchagua Chico, canton Saquisilí, provincia de Cotopaxi, periodo 2014-2015 - Sampedro Yugcha, Segundo Cristóbal (2015)
The present study had as aim to monitor existing species of birds and reptiles in the high area of the community of Chico Canchagua, Also to determine the ecological niche of the species found. For which the identification and a study area tour was carried out and the exact area where the monitoring of species of wildlife was determined which was divided in 6 quadrants. Additionally structured surveys to the population of the Community were applied. Consecutively 18 monitoring points were selected at random (birds) and 24 (reptiles); in bird the monitoring was carried out by the point count method of infinite radius, in the reptiles pitfall and loop methods were used….